Acta Universitatis Danubius. Œconomica, Vol. 15, No. 1 - 4: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
The study investigates the link between financial development, investment and energy consumption in Nigeria. The aim of the study is to re-examine financial development and energy consumption model by considering investment as a factor that contributes to more energy demand for consumption. The study employs an annual data within the period 1981 and 2015. The Auto-regressive Distributed Lag (ARDL) Method is used to analyse the data. From the results, financial development had a negative impact on energy consumption both in the short-run and the long-run. Investment has a positive significant impact on energy consumption in the short-run, while it was significantly negative in the long-run. GDP in the long-run and short-run positively relates with energy consumption. Population growth rate in the short-run negative impact on energy consumption, while in the long-run was positive. The findings propel the conclusion that financial development and investment are an important determinant of energy consumption in Nigeria and government should consider a policy that incorporate credit availability on energy issues into its plan.